2015
DOI: 10.1024/0300-9831/a000233
|View full text |Cite
|
Sign up to set email alerts
|

Association of Major Dietary Patterns with General and Abdominal Obesity in Iranian Patients with Type 2 Diabetes Mellitus

Abstract: This study shows that in patients with type 2 diabetes mellitus, a healthy dietary pattern is inversely associated and an unhealthy dietary pattern is directly associated with general obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…According to this study, women who followed a "healthy" dietary pattern consumed more vegetables, fish, seaweed, fruits, and soy products than those who did not, which aligns with previous studies. Consistent with the "healthy" pattern identified in this study, "prudent" and "healthy" patterns have been previously reported to be inversely associated with the risk of abdominal obesity in older Brazilians [31], Chinese adults [32,33], and Iranian patients with type 2 diabetes [34]. According to a recent systematic review and meta-analysis, which included 13 studies, individuals in the highest category of the "healthy/prudent" patterns had a 0.81 times lower risk of abdominal obesity compared with those in the lowest category (pooled odds ratio [OR]: 0.81, 95% CI: 0.66-0.96) [35].…”
Section: Discussionsupporting
confidence: 90%
“…According to this study, women who followed a "healthy" dietary pattern consumed more vegetables, fish, seaweed, fruits, and soy products than those who did not, which aligns with previous studies. Consistent with the "healthy" pattern identified in this study, "prudent" and "healthy" patterns have been previously reported to be inversely associated with the risk of abdominal obesity in older Brazilians [31], Chinese adults [32,33], and Iranian patients with type 2 diabetes [34]. According to a recent systematic review and meta-analysis, which included 13 studies, individuals in the highest category of the "healthy/prudent" patterns had a 0.81 times lower risk of abdominal obesity compared with those in the lowest category (pooled odds ratio [OR]: 0.81, 95% CI: 0.66-0.96) [35].…”
Section: Discussionsupporting
confidence: 90%
“…2-4 Indeed, previous studies have shown that nutrition status is closely related to the inception of these diseases. 5-8 To clarify other positive aspects of this healthy diet, examining the DASH diet based on other dietary quality indices will be helpful.…”
Section: Introductionmentioning
confidence: 99%